Impact of Interprofessional Primary Care Practice on Patient Outcomes: A Scoping Review. (June 2020) - McCutcheon, Livia R. M.; Haines, Stuart T.; Valaitis, Ruta; Sturpe, Deborah A.; Russell, Grant; Saleh, Ahlam A.; Clauson, Kevin A.; Lee, Jeannie K.
Systematic reviews have provided some insight into the impact of interprofessional collaborative practice on patient outcomes. Despite strong interest in interprofessional collaborative practice, relatively little is known about its impact in primary care settings. This scoping literature review describes the essential elements of an interprofessional primary care practice and explores what is known about its impact on patient care including clinical, humanistic, and economic outcomes. We completed a review of the literature examining the breadth of knowledge related to interprofessional collaborative practice in primary care settings. A search was conducted to identify studies based on predefined criteria. A total of 51 studies met the criteria. A total of 27 studies reported a significantly positive clinical outcome with the interprofessional collaborative practice model, 27 studies reported no difference, and one study reported negative outcome in mortality. A total of 15 studies reported a significantly positive humanistic outcome. There was little to no difference in economic outcomes. This study provides new insights for future research that examines the impact of interprofessional primary care practice.